The use of quantitative method in studies maps by date (Journal of the College of Basic Education, 2022)
Use the quantitative method in cartographic studies by addressing new research methods. It was used to solve geographical problems, as the emergence of statistical maps was associated with what is called (the revolution in quantity in geography), and the Arabs preceded others in defining this concept in what is called (geographical). Mathematical (and as an example of that (measuring the midday line, the dimensions of the globe, and the division of regions) Relying on quantitative methods that confirm their precedence and leadership in this field.